Entrepreneurial Profile and Constraint Analysis of Farm and Non-farm Sectors Entrepreneurial Training Programmes in Krishi Vigyan Kendra and Rural Development & Self Employment Training Institute (Indian Journal of Extension Education, 2020)
Even though research has proven beyond all reasonable doubt that entrepreneurship can boost the economy of many nations, this has not been true for many due to the challenges which impede entrepreneurship programmes in both farm and non-farm sectors. A study was therefore conducted with the aim of analyzing these constraints. An interview schedule was used to collect information from 120 entrepreneurs, (60 farm and 60 non-farm entrepreneurs). Result shows that the mean age of farm entrepreneurs was 38 years whereas the mean age for non-farm entrepreneurs was 28 years. In RUDSETI farm sector, more than three-fifths (66.6%) of the entrepreneurs had an annual income of less than 1 lakh whereas, in the non-farm sector, half (50.0%) of the entrepreneurs had an annual income of more than 3 lakh. Similarly in KVK, farm sector, close to half (46.7%) of the entrepreneurs had an annual income of more than 3 lakhs whereas in the non-farm sector close to half (46.7%) of the entrepreneurs had an annual income of 1-2 lakh. In RUDSETI farm and non-farm sector, all (100.0%) and half (50.0%) of the entrepreneurs had 1-3 years of entrepreneurial experience respectively. Similarly in KVK farm and non-farm sectors, 53.3 per cent and 76.7 per cent of the entrepreneurs had an entrepreneurial experience of 1-3 years respectively. It was found that the highest-ranked constraint in the farm sector was lack of market information (71.0%) and lack of financial resources (69.5) whereas in the non-farm sector, it was observed that the constraint which had the highest rank was lack market information (68.1) and lack of financial resources (63.4%).